(untitled) (Journal of Business Management and Accounting, 2021)
The aim of this study is to identify and analyse internal audit competency requirement for effective auditing performance in tax administration. To achieve this, a case study methodology was employed to carry out a face-to-face interview with 9 internal auditors of the Federal Inland Revenue Service (FIRS) Nigeria. The collected data was analysed using Nvivo qualitative software. The findings of the study show that qualification, knowledge and skills are the three major indicators of internal auditors’ competency in performing effective auditing functions in tax administration. This study implies that to achieve a successful performance of internal auditing in the 74 Journal of Business Management and Accounting, Vol. 11, Number 2 (July) 2021, pp:73–94 FIRS, competent internal audit staffs are highly needed for effective internal auditing performance.